John Bigelow papers - Bigelow, John, 1854-1936.; Bigelow, John, 1817-1911.; Isthmian Canal Commission (U.S.)
Correspondence, writings, research notes, photostatic copies of manuscripts in foreign archives, bibliographical material, pamphlets, clippings, maps, drawings, photographs, and other papers relating primarily to canals, especially the Panama Canal and Suez Canal. Includes material pertaining to the Nicaragua Canal, Tehuantepec Canal, Saint Lawrence Seaway, and canal tolls. Subjects include Robert E. Lee; the U.S. Constitution; American Revolution, especially the Saratoga Campain, N.Y., 1777; U.S. Civil War; Monroe Doctrine; expansion; military education, history, and policy; American foreign policy including relations with Great Britain; World War I; international law; early history of civilization; Egypt; and Latin America. Includes material pertaining to Bigelow's service in the Massachusett's Militia; an abstract from the diary of Bigelow's father, John Bigelow, relating to Panama (1886-1911); records of the Isthmian Canal Commission; and maps of the Old World and New World.
Library of Congress Geography and Map Division.
Army officer, educator, and author.
Collection material in English, French, German, Italian, and Spanish.
Finding aid available in the Library of Congress Manuscript Reading Room.
Keywords: Lee, Robert E. -- 1807-1870.; Massachusetts. -- Militia; United States. -- Juvenile literature; Canals; Canals -- Rates and tolls; History, Ancient; Military education; Military history; Military policy; International law; Monroe doctrine; Saratoga Campaign, N.Y., 1777.; World War, 1914-1918.; Eastern Hemisphere -- Maps; Egypt -- History; Great Britain -- Foreign relations -- United States; Latin America -- History; New York (State) -- History -- Revolution, 1775-1783.; Nicaragua Canal (Nicaragua); Panama -- History -- To 1903.; Panama Canal (Panama); Saint Lawrence Seaway; Suez Canal (Egypt); Tehuantepec Canal (Mexico); United States -- Foreign relations; United States -- Foreign relations -- Great Britain; United States -- History -- Civil War, 1861-1865.; United States -- History -- Revolution, 1775-1783.; United States -- History -- Revolution, 1775-1783 -- Campaigns; United States -- Territorial expansion; Western Hemisphere -- Maps; Army officers; Authors; Educators